Systematic Review of Character Education Integrating Islamic and Global Moral Values - Hermawan, A. Heris; Tatang Muh Nasir; Mohamad Sabarudin; Yusuf Sugiana; Rachanda Ambya; Aan Hasanah; Bambang Samsul Arifin (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Character education is essential in shaping students’ morals amid the challenges of globalization, which often undermines moral values. Issues such as declining respect for authority, delinquency, and low empathy reflect a moral crisis among youth. This study aims to examine the urgency of character education from an Islamic perspective and to identify effective strategies for its implementation. Using a systematic literature review (SLR) method, 77 scientific articles published between 2019 and 2025 were analyzed. The study focuses on three dimensions: internalization of values in families, institutionalization in schools, and externalization in students' social behavior. Findings show that character education strongly influences moral development through value-based family upbringing, integrated school programs, and positive social interaction. However, challenges include limited parental engagement and inadequate teacher training. The study concludes that an integrated effort between family, school, and community is crucial to ensure sustainable and effective character education that aligns with both Islamic values and global moral frameworks.